I'm having some trouble understanding the layout of these "function" problems.
In the following question, f(x) = f(x^2) ... doesn't this mean that f(2) = f(2^2) = 4?
Therefore, in answer #1, the left side is:
f(4) which should equal (4^2) =16. The right side has (2^2)*(2^2) = 4*4 =16.
Perhaps I'm missing something here and would appreciate any clarification.
the question talks about the relation between f(x) and f(x^2)
it doesnt say that f(x) = x^2 right?
so f(2) = f(2^2) = f(4) and not the value 4.
if f(x) = f(x^2)
then f(x^2) = f([x^2]^2) = f(x^4) ... so on and so forth.
B satisfies this.
f(-2) = f([-2]^2) = f(4) = f(4^2) = f(16)
The Legion dies, it does not surrender.